Gut microbiota profile in adults with abdominal obesity and non-abdominal obesity: links to body composition and macronutrient intake in Semarang, Indonesia—a brief research report - Fadhillah, Farhan Syafiq; Arafat, Fariz Budi; Maharani, Nani; Fadhilah, Jihan; Zariyah, Hainun; Sobirin, Mochamad Ali; Tsutsui, Hiroyuki; Wibowo, Adi; Juniarto, Achmad Zulfa; Pramono, Adriyan (Frontiers in Nutrition, 2025)
BackgroundAbdominal obesity is a significant risk factor for metabolic syndrome and cardiovascular diseases, with increasing evidence highlighting the role of gut microbiota in its development. In Indonesia, where 23.4% of adults are obese, few studies have examined the gut microbiota in relation to abdominal obesity, particularly in the context of unique dietary patterns. This pilot study investigated the gut microbiota composition in adults with abdominal obesity in Semarang, Indonesia, and its associations with body composition and macronutrient intake.MethodsThis cross-sectional study was conducted in Semarang and included 46 adults aged 20–50 years, categorized by abdominal obesity status (22 with abdominal obesity and 24 without). Anthropometric measurements, body composition, and dietary intake were assessed. Gut microbiota profiles were analyzed using 16S rRNA gene sequencing of fecal samples.FindingsIn the Semarang population, individuals with abdominal obesity had higher visceral fat (12.32 ± 3.44% vs. 6.96 ± 2.91%) compared to those without abdominal obesity. Prevotella_9 copri was positively associated with visceral fat (r = 0.206, p = 0.169), a finding that differs from studies conducted outside Indonesia, potentially showing the uniqueness of the profile.ConclusionThe correlation of Prevotella_9 copri in subjects from Semarang, Indonesia, differs from findings in other studies, providing a potential unique gut microbiota profile in the Indonesian population and providing a platform for future studies to clarify these hypotheses. Larger longitudinal studies are needed to validate these findings and establish causality.